2016
DOI: 10.1111/1467-8578.12143
|View full text |Cite
|
Sign up to set email alerts
|

The experiences of learning, friendship and bullying of boys with autism in mainstream and special settings: a qualitative study

Abstract: This study aimed to explore experiences of learning, friendships and bullying of boys with autism attending specialist and mainstream schools, and those of their parents. Semi-structured interviews were conducted with 11 boys with autism, aged 11 to 17 years, and nine of their mothers. Thematic analysis identified four key themes relating to experiences of friendships and bullying, risk factors, protective factors and outcomes. Overall, the findings indicated that five of the 11 participants had been subjected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 26 publications
(31 reference statements)
2
30
0
Order By: Relevance
“…This study involved the autistic community at a number of levels. First, the research questions emerged from existing literature and previous interviews with autistic young people and their parents ( Cook et al, 2016 , 2017 ); second, these research questions were developed and formulated for this study in collaboration with a working group established by the National Autistic Society (NAS) to evaluate the effectiveness of the newly opened Cullum Centres. Third, NT and autistic children helped shape the research materials through a pilot process and gave their feedback on the vignettes and questions asked.…”
Section: Methodsmentioning
confidence: 99%
“…This study involved the autistic community at a number of levels. First, the research questions emerged from existing literature and previous interviews with autistic young people and their parents ( Cook et al, 2016 , 2017 ); second, these research questions were developed and formulated for this study in collaboration with a working group established by the National Autistic Society (NAS) to evaluate the effectiveness of the newly opened Cullum Centres. Third, NT and autistic children helped shape the research materials through a pilot process and gave their feedback on the vignettes and questions asked.…”
Section: Methodsmentioning
confidence: 99%
“…Inclusion criteria comprised females in Years 7-13 with autism, who would be willing and able to engage with the questions in the interview and communicate their experiences, and one of their parents. A previous study was completed with boys (Cook, Ogden and Winstone 2016) exploring their experience of the same areas.…”
Section: Participantsmentioning
confidence: 99%
“…They expressed the view that inclusive education cannot be achieved for some children with EBD and suggested that special schools or wholly or partly separated facilities will probably always be needed. Additionally, Cook et al's () investigation in England of experiences of friendships, bullying and learning of boys with autism in mainstream and special settings, based on interviews with 11 boys with autism and with nine of their mothers, concluded that special schools facilitate social interactions and cope with bullying more appropriately. They recommended interventions in mainstream to promote a better school culture in which children with autism can flourish.…”
Section: Discussionmentioning
confidence: 99%
“…The review begins with a discussion of literature relating to changing policy and practice regarding the role of special schools, from Warnock's (1978) vision of the integration of children with special educational needs to the present day (Male & Rainer, 2007;Norwich & Gray, 2007;Norwich, 2007Norwich, , 2014; Galton & MacBeath, 2015). Secondly, research highlighting the benefits and challenges faced by special schools is investigated (Hornby & Witte, 2008;Parsons et al, 2009;Parsons, 2015;Day et al, 2012;Reed et al, 2012;Kelly et al, 2014;Black, 2014;Cook et al, 2016). Thirdly, research emphasising the value and challenges of inclusion in mainstream settings is reviewed (Frederickson et al, 2007;Lindsay et al, 2016;O'Hagan & Hebron, 2016;Broomhead, 2013Broomhead, , 2014de Graaf et al, 2013;Waddington & Reed, 2016;de Boer et al, 2013;Glazzard, 2014;Webster & Blatchford, 2015).…”
mentioning
confidence: 99%